Environmental Impacts of Waste Disposal: An Overview on the Disposal of Polyethylene Bags in Gusau City Zamfara State - Lawan Muhammad, Usman; Muhammad Shamsuddin, Ibrahim; Muhammad Yahaya, Kurfi; Nuhu, Ma’aruf (Journal of Evolutionary Science, 2019)
The environmental impacts of waste disposal of polyethylene bags and seasonal variation of polyethylene disposal in Gusau City of Zamfara state, Nigeria was investigated. General public waste disposals from homes, schools and daily markets, were randomly selected for data collection. The data showed that polyethylene waste is generated more in the dry season than the wet season. The result also showed that table water sachet has 75% disposal. This is because, sachet water is cheap and consumed throughout the year with very little seasonal variation while at homes and markets also, displayed a very interesting pattern. The study revealed that in the market, polyethylene for table water sachets (10%) was the least, followed by ice cream sachets (6%), assorted items (5%) and biscuits wrappers (4%). On the other hand, the results showed that, at home, polyethylene for assorted items was the highest (61%), closely followed by biscuit wrappers (20%), table water sachets (14%) and ice cream wrappers (5%) respectively. Polyethylene waste poses various threats to public health and adversely affects flora and fauna as well as the environment especially when it is not appropriately collected and properly disposed. And based on this research, it was found that most of the public do not know the advantages, disadvantages and the health effects of rampant and improper disposal of polyethylene bags. It is concluded that aggressive campaign and enlightenment of the masses on the threats posed by polyethylene bags pollution should be carried out to prevent further negative environmental impact.
Keywords: polyethylene; pollution; environmental; impact; campaign; enlightenment